1999
DOI: 10.1046/j.1464-5491.1999.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐action profile of the soluble, fatty acid acylated, long‐acting insulin analogue NN304

Abstract: Injection of NN304 at different doses resulted in an increase in total NN304 concentration in a linear dose-response effect and a more even metabolic effect than NPH-insulin. However, we found no clear dose-response in its metabolic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 5 publications
3
80
0
2
Order By: Relevance
“…This prolonged duration of action complements findings from kinetic studies showing that insulin detemir has a flatter timeaction profile than NPH (26), reaching a peak effect almost 90 min later than NPH (26). From these profiles, the duration of action of insulin detemir appears to be long enough to cover nighttime basal insulin requirements.…”
Section: Variability Of Glycemic Controlsupporting
confidence: 77%
“…This prolonged duration of action complements findings from kinetic studies showing that insulin detemir has a flatter timeaction profile than NPH (26), reaching a peak effect almost 90 min later than NPH (26). From these profiles, the duration of action of insulin detemir appears to be long enough to cover nighttime basal insulin requirements.…”
Section: Variability Of Glycemic Controlsupporting
confidence: 77%
“…These insulin analogs make use of different principles for achieving a protracted insulin profile, such as changing the isoelectric point (insulin glargine) or acylation of the insulin molecule (insulin detemir). Previous studies have confirmed both a delayed and a sustained blood glucoselowering effect with insulin detemir compared with NPH insulin in healthy subjects (10,11). However, the results show that a higher molar dose of insulin detemir is needed to achieve comparable glycemic control similar to that observed with NPH insulin (10).…”
mentioning
confidence: 75%
“…Analytical methods The total concentrations of free and bound insulin detemir in serum were measured with an insulin detemir-specific ELISA [13]. Concentrations of serum human insulin and C-peptide were analysed using an insulin ELISA assay (Dako, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%